Chapter One (The Wrong Kind of ) Gonorrhea in Antiquity - Flemming, Rebecca (University of Rochester Press, 2019)
Studying the relationship between disease and fertility in antiquity is challenging. The first difficulty is establishing the presence, and then prevalence, of any particular condition before an assessment can be made of its demographic impact. In the case of what are now called sexually transmitted infections (STIs), the empirical obstacles to identifying such infections in the classical world are exacerbated by the moralizing that attends discussions of sexual practice and that has so strongly characterized the ways sexual behavior and pathology have been, and continue to be, conceptually conjoined. Julius Rosenbaum's influential and exhaustive nineteenth-century exploration of the ancient history of syphilis (broadly construed), for example, is based on the assumption that venereal diseases are caused by the "abuse" of the genital organs for nonprocreative purposes. Their history is, therefore, the history of human "lasciviousness and debauchery," and there was so much of that in classical Greece and Rome that syphilis and all kinds of genital afflictions necessarily followed.